2001
DOI: 10.1002/ana.102.abs
|View full text |Cite
|
Sign up to set email alerts
|

Absence of N‐acetylaspartate in the human brain: Impact on neurospectroscopy?

Abstract: N-acetylaspartate (NAA) contributes to the most prominent signal in proton magnetic resonance spectroscopy (1H-MRS) of the adult human brain. We report the absence of NAA in the brain of a 3-year-old child with neurodevelopmental retardation and moderately delayed myelination. Since normal concentration of NAA in body fluids is hardly detectable, 1H-MRS is a noninvasive technique for identifying neurometabolic diseases with absent NAA. This report puts NAA as a neuronal marker to question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 0 publications
0
47
1
Order By: Relevance
“…Conditioning pulse protocols have reliably demonstrated reduced intracortical inhibition as a characteristic feature of ALS [Menon et al, 2015; Yokota et al, 1996; Ziemann et al, 1997], which may be partly ameliorated by reducing glutamatergic influence through administration of Riluzole—the only licensed disease‐modifying therapy in ALS [Stefan et al, 2001; Vucic et al, 2013a]. Postmovement beta rebound corresponds well to a period of reduced cortico‐spinal tract excitability, and the present data suggest that ALS patients differ in the speed of transition to this state after movement.…”
Section: Discussionmentioning
confidence: 99%
“…Conditioning pulse protocols have reliably demonstrated reduced intracortical inhibition as a characteristic feature of ALS [Menon et al, 2015; Yokota et al, 1996; Ziemann et al, 1997], which may be partly ameliorated by reducing glutamatergic influence through administration of Riluzole—the only licensed disease‐modifying therapy in ALS [Stefan et al, 2001; Vucic et al, 2013a]. Postmovement beta rebound corresponds well to a period of reduced cortico‐spinal tract excitability, and the present data suggest that ALS patients differ in the speed of transition to this state after movement.…”
Section: Discussionmentioning
confidence: 99%
“…This and many other observations have led many to conclude that NAA is a neuronal marker. This conclusion was questioned by Martin et al 52 who reported MR spectra with little or no NAA in a three year-old patient with developmental deficits. This report was followed by several letters to the editor discussing the role of NAA as a neuronal marker.…”
Section: N-acetylaspartatementioning
confidence: 95%
“…Proton ( 1 H) magnetic resonance spectroscopy (MRS) of the human brain in vivo makes it possible to measure the pool size of certain chemical constituents presumed to be metabolically important, including amino acids (eg Nacetylaspartate or NAA), amines, sugars, and bioenergetic metabolites (Martin et al, 2001). The promise inherent to measuring metabolites in the living brain has made MRS methodology very attractive to investigators interested in psychiatric illness.…”
Section: Introductionmentioning
confidence: 99%